Analysis of the Influence of Discipline, Competence and Workload on the Employee Performance at Kelas Pintar Startup - Ardian, Ardian; Sary, Fetty Poerwita (International Journal of Social and Management Studies, 2024)
: Kelas Pintar is a technology-based educational solution designed to increase students' understanding of subject matter and aims to improve the quality of human resources with the best educational reference for a better nation. To achieve this goal, maximum performance is required by employees. Therefore, the authors conducted research with the hypothesis that there is a significant influence between discipline, competence, and workload on the performance of Kelas Pintar Startup employees. The purpose of this study was to find out how much influence discipline, competence and workload have on the performance of Kelas Pintar Startup employees, both partially and simultaneously. The research method used is quantitative. The sampling technique used was proportionated stratified random sampling, where the sample was obtained by the portion of the population, namely 168 respondent. This research uses Structural Equation Modeling with Partial Least Square Technique (SEM-PLS). While the research analysis uses descriptive analysis, making path models, analyzing outer models, analyzing inner models, and testing hypotheses. The results of the study prove that the path coefficient (original sample) for discipline (X1) is 0.440 or 44%, competence is 0.344 or 34.4% and workload is 0.208 or 20.8%. So it can be interpreted that the variables of discipline, competence and workload have a significant positive effect on employee performance.